Correlation of Tuberculin Conversion In Children Beyond 5 Years of Age With Active Tuberculous Infection - B. N. Gaind; A. M. Berry; S. Ghosh (Paediatrica Indonesiana, 1984)
Tuberculosis is a serious and crippling disease in children. It can be fatal. It takes a beningn or a latent course in childhood, as it lies dormant and may flare up during adolescence. Female children are more prone during onset of mensturation. Contact with a patient of tuberculosis is present in about 22% children. Children with a history of measles in the recent past are more susceptible to get the tuberculous infection. There is no correlation between the size of tuberculin reaction and the severity of the disease. Parenchymatous lesions of the lungs are not that common as those of intrathoracic lymph nodes.